33.3k views
2 votes
Question 1*

1 point
For questions 1-5, let f(x) = x2 +6x + 7, g(x) = 8x2 – 2, h(x) = 3x + 4, and
k(x) =
x-3
2x+1
1.
Evaluate f(2) - g(2). k(2)

User Stames
by
6.0k points

1 Answer

4 votes

Given expressions;

f(x) = x² + 6x + 7

g(x) = 8x² - 2

h(x) = 3x + 4

k(x) = x - 3

Find f(2) - g(2). k(2)

f(2) = 2² + 6(2) + 7 = 23

g(2) = 8(2)² - 2 = 30

k(2) = 2 - 3 = -1

Now, f(2) - g(2). k(2) = 23 - (30)(-1)

= 53

The solution to the problem is 53

User Wootsbot
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.